Current state of INRA research on olive trees in Morocco - Faouzi Bekkaoui; Lhassane Sikaoui; Abdelaziz Bouizgaren; Abderraouf El Antari; Ahmed El Bakkali; Yamna Ouguas; Hayat Zaher; Ahmed Ait Hmida (African and Mediterranean Agricultural Journal - Al Awamia)
The olive tree is the main fruit species cultivated in Morocco representing 65% of the national fruit trees area with 1 098 000 (1.1 million) hectares. The olive sector contributes over 6.8 billion MAD in added value, around 5% of the national agricultural product (GNP) and around 19% of total edible oil consumption. Therefore, the olive sector is an important component of the national strategies, Plan Maroc Vert (PMV, 2008-2019) and currently Generation Green (2020-2030) aimed at modernizing and developing olive sector by improving olive oil productivity and quality and thereby increasing farmer’s income. For this reason, a contract program consistent with the Generation Green strategy foundations was signed with a Moroccan interprofessional organization ‘Interprolive’ aimed to develop and modernize the olive sector over the 2020-2030 period. This contract program gives priority to the human element and sustainable eco-efficient agricultural agriculture. Its main objective is enhancing competitiveness of olive sector by improving productivity and quality of olive products and olive chain value. Therefore, strengthening research and development related to olive sector is required. INRA as a public research institution is engaged in implementation of Generation Green strategy by carrying out a mid-term olive research project to promote the olive-growing sector. This olive research program is carried out at INRA Marrakech and INRA Meknes and includes five main topics: (i) Conservation and valorization of genetic resources; (ii) Irrigation and fertilization management; (iii) Integrated pest management; (iv) Olive oil quality and valorization; and (v) Olive value chain analysis. The research results from these activities have contributed to improving the productivity, sustainability, and competitiveness of the olive sector.